Sequential Isolation of Saturated, Aromatic, Resinic, and Asphaltic Fractions Degrading Bacteria from Oil Contaminated Soil in South Sumatera - Munawar, Munawar; Aditiawati, Pingkan; Astuti, Dea Indriani (Makara Journal of Science, 2012)
Sequential isolation has been conducted to obtain isolates of saturated, aromatic, resin, and asphaltene fractions degrading bacteria from oil contaminated sites. Five soil samples were collected from South Sumatera. These bacterial isolates were obtained using soil extract medium enriched with oil recovery or remaining-oil recovery degradated (ROD) as sole carbon and energy sources according to the isolation stage as the isolation medium. ROD at the end of every isolation stage analyzed oil fractions by use of the SARA analysis method. Six isolates of bacteria have been selected, one isolate was fraction saturates degrading bacteria that are Mycobacterium sp. T1H2D4-7 at degradation rate 0.0199 mgs/h with density 8.4x106 cfu/g from stage I. The isolate T2H1D2-4, identified as Pseudomonas sp. was fraction aromatics degrading bacteria at accelerate 0.0141 mgs/h with density 5.1x106 cfu/g are obtained at stage II. Two isolates namely Micrococcus sp. T3H2D4-2 and Pseudomonas sp. T1H1D5-5 were fraction resins degrading bacteria by accelerate 0.0088 mgs/h at density 5.6x106 cfu/g and 0.0089 mgs/h at density 5.7x106 cfu/g are obtained at stage III. Isolation of stage IV has been obtained two isolates Pseudomonas sp. T4H1D3-1and Pseudomonas sp. T4H3D5-4 were fraction asphaltenes degrading bacteria by accelerate 0.0057 mgs/h at density 5.6x106 cfu/g and accelerate 0.0058 mgs/h at density 5.7x106 cfu/g.